2010
DOI: 10.2147/prom.s14861
|View full text |Cite
|
Sign up to set email alerts
|

Nail psoriasis as a severity indicator: results from the PsoReal study

Abstract: Background:Although nail psoriasis affects a substantial proportion of psoriasis patients and causes significant psychologic distress, few epidemiologic data characterizing patients with nail involvement are available. The aim of this research was to elucidate differences between patients with nail psoriasis and those without any nail involvement, taking quality indicators of health care from the patient’s perspective into account.Methods:In total, 2449 patient members of the Deutscher Psoriasis Bund, the larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
2
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 31 publications
(36 reference statements)
8
57
2
5
Order By: Relevance
“…[2,6,7] Nail psoriasis occurs more often in patients with more severe psoriasis and there is a positive correlation between the severity of nail lesions and the severity of joint and skin symptoms. [2,8,9] However, nail abnormalities may be the only manifestation of psoriasis and are also frequently seen in patients with mild disease. [2] Nail involvement may manifest as nail pitting (small depressions in the nail plate), nail bed discoloration ('salmon spots' or 'oil drops'), subungual hyperkeratosis, nail plate thickening and crumbling, onycholysis, splinter hemorrhages, leukonychia, and red spots in the lunula.…”
Section: Nail Psoriasismentioning
confidence: 99%
“…[2,6,7] Nail psoriasis occurs more often in patients with more severe psoriasis and there is a positive correlation between the severity of nail lesions and the severity of joint and skin symptoms. [2,8,9] However, nail abnormalities may be the only manifestation of psoriasis and are also frequently seen in patients with mild disease. [2] Nail involvement may manifest as nail pitting (small depressions in the nail plate), nail bed discoloration ('salmon spots' or 'oil drops'), subungual hyperkeratosis, nail plate thickening and crumbling, onycholysis, splinter hemorrhages, leukonychia, and red spots in the lunula.…”
Section: Nail Psoriasismentioning
confidence: 99%
“…However, it is reported that in patients with psoriasis nail involvement in addition to patient age was significantly related to disease severity (16). Given that all of the patients in this study were in severe stages of acne vulgaris and patients with moderate and mild acne vulgaris were not included in present study, no judgment is possible based on the severity and extent of acne lesions in these people and its relationship with nail lesions.…”
Section: Discussionmentioning
confidence: 86%
“…M. Radtke и соавт. [15] показали, что псориаз ногтей является предикто-ром тяжелого течения псориаза и увеличивает вероятность ПсА до 70-80%. V. Azevedo и соавт.…”
Section: Discussionunclassified